R&D expenditure and productivity in the Mexican manufacturing industry - Cabral, René; González, Franco Jair (Estudios Económicos de El Colegio de México, 2014)
We study the effects of R&D on productivity across a sample of 17 Mexican manufacturing sectors from 1994 to 2007. Employing panel data methods we find some interesting results. First, ordinary least squares estimates suggest a strong link between R&D expenditure and productivity. Second, after controlling for heterogeneity and endogeneity problems such evidence disappears. Third, partitioning our sample according to R&D intensity criteria, we even observe negative effects on productivity from those industries that employ that resource more intensively.